Vitamin D status in full-term exclusively breastfed infants versus full-term breastfed infants receiving vitamin D supplementation in Thailand: a randomized controlled trial - Chayatat Ruangkit; Sukrit Suwannachat; Pornchanok Wantanakorn; Napapailin Sethaphanich; Surapat Assawawiroonhakarn; Oraporn Dumrongwongsiri (BMC, 2021)
Abstract Background Many international medical organizations recommend vitamin D supplementation for infants, especially exclusively breastfed infants. In Thailand, however, data regarding the vitamin D status in Thai infants are lacking. Such data would help to support physician decisions and guide medical practice. Methods Full-term, exclusively breastfed infants were randomized into two groups at 2 months of age to continue exclusive breastfeeding either without vitamin D supplementation (control group, n = 44) or with vitamin D3 supplementation at 400 IU/day (intervention group, n = 43) until 6 months of age. At 6 months, the serum vitamin D (25OHD) of the infants and their mothers, serum bone marker, and infants' growth parameters were compared between the two groups. Results The infants' serum 25OHD concentration was lower in the control group than intervention group (20.57 ± 12.66 vs. 46.01 ± 16.42 ng/mL, p < 0.01). More infants had vitamin D sufficiency (25OHD of > 20 ng/mL) in the intervention group than control group (93.0% vs. 43.2%, p < 0.01). There were no significant differences in the maternal 25OHD concentrations between the control and intervention groups (25.08 ± 7.75 vs. 23.75 ± 7.64 ng/mL, p = 0.42). Serum calcium, phosphorus, intact parathyroid hormone, alkaline phosphatase, and infants' growth parameters were comparable between the two groups. After adjustment for the confounding factors, 25OHD concentration in the intervention group was 25.66 ng/mL higher than the control group (95% confidence interval, 19.07-32.25; p < 0.001). Vitamin D supplement contributed to an 88.7% decrease in the prevalence of vitamin D insufficiency/deficiency (relative risk, 0.11; 95% confidence interval, 0.04-0.35; p < 0.01). Conclusions Most full-term, exclusively breastfed Thai infants have serum vitamin D concentration below sufficiency level at 6 months of age. However, vitamin D supplementation (400 IU/day) improves their vitamin D status and prevents vitamin D deficiency. Trial registration The study was pre-registered in the Thai Clinical Trials Registry ( TCTR20190622001 ) on 22/06/2019.